Dark Photocatalysis: Storage of Solar Energy in Carbon Nitride for Time‐Delayed Hydrogen Generation. Issue 2 (8th December 2016) - Lau, Vincent Wing‐hei; Klose, Daniel; Kasap, Hatice; Podjaski, Filip; Pignié, Marie‐Claire; Reisner, Erwin; Jeschke, Gunnar; Lotsch, Bettina V.
Abstract: While natural photosynthesis serves as the model system for efficient charge separation and decoupling of redox reactions, bio‐inspired artificial systems typically lack applicability owing to synthetic challenges and structural complexity. We present herein a simple and inexpensive system that, under solar irradiation, forms highly reductive radicals in the presence of an electron donor, with lifetimes exceeding the diurnal cycle. This radical species is formed within a cyanamide‐functionalized polymeric network of heptazine units and can give off its trapped electrons in the dark to yield H2, triggered by a co‐catalyst, thus enabling the temporal decoupling of the light and dark reactions of photocatalytic hydrogen production through the radical′s longevity. The system introduced here thus demonstrates a new approach for storing sunlight as long‐lived radicals, and provides the structural basis for designing photocatalysts with long‐lived photo‐induced states. Abstract : Live long and prosper : A cyanamide‐functionalized carbon nitride can form ultra‐long‐lived radicals under solar irradiation in the presence of an electron donor. This longevity enables the temporal decoupling of the two half reactions in the photo‐redox production of hydrogen.